A review of dosimetry used in epidemiological studies considered to evaluate the linear no-threshold (LNT) dose-response model for radiation protection. (3rd October 2017) - Till, John E.; Beck, Harold L.; Grogan, Helen A.; Caffrey, Emily A.
Abstract: Background: Accurate dosimetry is key to deriving the dose response from radiation exposure in an epidemiological study. It becomes increasingly important to estimate dose as accurately as possible when evaluating low dose and low dose rate as the calculation of excess relative risk per Gray (ERR/Gy) is very sensitive to the number of excess cancers observed, and this can lead to significant errors if the dosimetry is of poor quality. By including an analysis of the dosimetry, we gain a far better appreciation of the robustness of the work from the standpoint of its value in supporting the shape of the dose response curve at low doses and low dose rates. This article summarizes a review of dosimetry supporting epidemiological studies currently being considered for a re-evaluation of the linear no-threshold assumption as a basis for radiation protection. The dosimetry for each study was evaluated based on important attributes from a dosimetry perspective. Our dosimetry review consisted of dosimetry supporting epidemiological studies published in the literature during the past 15 years. Based on our review, it is clear there is wide variation in the quality of the dosimetry underlying each study. Every study has strengths and weaknesses. The article describes the results of our review, explaining which studies clearly stand out for their strengths as well as common weaknesses among all investigations. Purpose: To summarize a review of dosimetry used in epidemiological studies being considered by the National Council on Radiation Protection and Measurements (NCRP) in an evaluation of the linear no-threshold dose-response model that underpins the current framework of radiation protection. Materials and methods : The authors evaluated each study using criteria considered important from a dosimetry perspective. The dosimetry analysis was divided into the following categories: (1) general study characteristics, (2) dose assignment, (3) uncertainty, (4) dose confounders (5) dose validation, and (6) strengths and weaknesses of the dosimetry. Our review focused on approximately 20 studies published in the literature primarily during the past 15 years. Results: Based on the review, it is clear there is wide variation in the quality of the dosimetry underlying each study. Every study has strengths and weaknesses. This paper describes the results of our review, identifies common weaknesses among all investigations, and recognizes studies that clearly stand out for their overall strengths. Conclusions: The paper concludes by offering recommendations to investigators on possible ways in which dosimetry could be improved in future epidemiological studies.